Pengaruh Teknologi Blockchain Terhadap Tingkat Keaslian Ijazah - Rahardja, Untung; Harahap, Eka Purnama; Christianto, Dennies Dwi (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2020)
Every person who has completed his formal education will certainly get a certificate, the certificate is very important to continue to the next level of education or to find work. However, there are still a handful of people who take actions against the law that is falsifying a certificate for a specific purpose, so that it will produce workers who do not have the quality to occupy a certain position. Where certificates are indeed very easy and inexpensive to fake but are expensive enough to prove their authenticity. Using blockchain technology is expected to overcome these problems so that it can be difficult for someone to fake a certificate and can help companies to prove the authenticity of certificates from prospective employees in just minutes and without having to pay a number of costs. It is hoped that the existence of this blockchain technology can continue to improve the quality of education in Indonesia.